2021
DOI: 10.21608/jsec.2021.154167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of country risk on foreign direct investment: Evidence from Egypt

Abstract: This paper examines the effect of country risk on Foreign Direct Investment (FDI) in Egypt during the years 2005-2015. We employ multiple regression analysis, to test the relationship among the selected variables that drive foreign direct investment flows to Egypt. FDI has always been an interesting topic for research; nevertheless, to the authors' knowledge, the impact of country risk on FDI has not been examined before in Egypt. Since FDI is a notable source of foreign currency income to the Egyptian economy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
3
1
0
1
Order By: Relevance
“…In particular, the result suggested that a 1% increase in the economic risk index score (which implies a decrease in economic risk) enhanced the FDI inflows by 0.919%, and vice versa. This result corroborated previous findings by Salehnia et al (2019) and Salem and Younis (2021), which showed that economic risk has a powerful effect on FDI inflows. The result further stressed the importance of maintaining high GDP levels, as well as optimal levels of the inflation rate, budget balance and current account for investment inflows to be enhanced in the V4.…”
Section: Panel Regression Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, the result suggested that a 1% increase in the economic risk index score (which implies a decrease in economic risk) enhanced the FDI inflows by 0.919%, and vice versa. This result corroborated previous findings by Salehnia et al (2019) and Salem and Younis (2021), which showed that economic risk has a powerful effect on FDI inflows. The result further stressed the importance of maintaining high GDP levels, as well as optimal levels of the inflation rate, budget balance and current account for investment inflows to be enhanced in the V4.…”
Section: Panel Regression Resultssupporting
confidence: 93%
“…The magnitudes of real GDP in the models suggested that it exerted a strong positive elastic impact on FDI in the V4. This research outcome is consistent with several studies that identified market size as a strong driver of FDI (Demirhan and Masca 2008;Khan and Akbar 2013;Meyer and Habanabakize 2018;Salem and Younis 2021;Wach and Wojciechowski 2016). The coefficient of natural resources was insignificant across the four models.…”
Section: Panel Regression Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Menurut hasil penelitiannya, negara dengan risiko politik yang tinggi dapat membuat investor kehilangan minatnya untuk berinvestasi dikarenakan investor khawatir akan dihadapkan oleh risiko kerugian yang dapat terjadi di negara tujuan. Pendapat yang berbeda dikemukakan oleh Dwinitasari & Sulasmiyati (2017) dan Salem & Younis, (2021), yakni risiko politik tidak memiliki pengaruh yang signifikan terhadap FDI. Hal ini disebabkan banyaknya faktor lain yang menjadi prioritas bagi investor untuk menanamkan investasinya seperti misalnya tersedianya sumber daya alam, sumber daya manusia, dan faktor -faktor lain yang dibutuhkan oleh investor.…”
Section: Pendahuluanunclassified